2013
DOI: 10.1371/journal.pone.0073298
|View full text |Cite
|
Sign up to set email alerts
|

Prednisolone as Preservation Additive Prevents from Ischemia Reperfusion Injury in a Rat Model of Orthotopic Lung Transplantation

Abstract: The lung is, more than other solid organs, susceptible for ischemia reperfusion injury after orthotopic transplantation. Corticosteroids are known to potently suppress pro-inflammatory processes when given in the post-operative setting or during rejection episodes. Whereas their use has been approved for these clinical indications, there is no study investigating its potential as a preservation additive in preventing vascular damage already in the phase of ischemia. To investigate these effects we performed or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 54 publications
3
21
0
Order By: Relevance
“…We observed suppressed expression of 27OHChol-induced M1 markers, and upregulation of the transcription and cell surface expression of CD163 and CD206, without further enhancement of the 27OHChol-induced expression of molecules. These results are consistent with previous reports that glucocorticoids generate M2 macrophages (20) and enhance transdifferentiation of macrophages towards the immune regulatory M2 phenotype (32). Taken together with previous publications, our findings suggest that prednisolone differentially regulates M1/M2 polarization of monocytes/macrophages.…”
Section: Discussionsupporting
confidence: 93%
“…We observed suppressed expression of 27OHChol-induced M1 markers, and upregulation of the transcription and cell surface expression of CD163 and CD206, without further enhancement of the 27OHChol-induced expression of molecules. These results are consistent with previous reports that glucocorticoids generate M2 macrophages (20) and enhance transdifferentiation of macrophages towards the immune regulatory M2 phenotype (32). Taken together with previous publications, our findings suggest that prednisolone differentially regulates M1/M2 polarization of monocytes/macrophages.…”
Section: Discussionsupporting
confidence: 93%
“…Lung preservation solution, such as low-potassium dextran (LPD) solution, is the most commonly used lung protective method during the cold ischemia phase. 3,4 Different perfusion pressures and perfusion methods for the donor could also improve lung graft function, 5 as could by using anti-platelet/endothelial cell adhesion molecule-1, 6 relaxin, 7 and steroids 8 during IRI. Additionally, hypothermia (4-10 C) is an important method for donor lung perseveration during the ischemia phase, 9,10 but the donor lung still could not be stored for a longer time.…”
Section: Introductionmentioning
confidence: 99%
“…It can be speculated that the high doses used in such studies blocked the proliferative and remodeling stages of MIRS, along with the inflammatory phase that was initially the intended target. Nowadays, a protective role for corticosteroids in MIRS has been described in both experimental [122,123] and clinical settings. Concordantly, a metaanalysis by Giugliano et al [124] showed this cardioprotective effect for corticosteroids in MIRS in patients.…”
Section: As Paracelsus Saidmentioning
confidence: 99%